Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Hoàng Thiên Bảo

\(\sqrt[3]{5\sqrt{2}+7}-\sqrt[3]{5\sqrt{2}-7}\)

alibaba nguyễn
16 tháng 11 2016 lúc 23:04

Đặt \(A=\sqrt[3]{5\sqrt{2}+7}-\sqrt[3]{5\sqrt{2}-7}=\sqrt[3]{7+5\sqrt{2}}+\sqrt[3]{7-5\sqrt{2}}\)

\(\Leftrightarrow A^3=14+3\left(-1\right)A\)

\(\Leftrightarrow\left(A^3-2A^2\right)+\left(2A^2-4A\right)+\left(7A-14\right)=0\)

\(\Leftrightarrow\left(A-2\right)\left(A^2+2A+7\right)=0\)

\(\Leftrightarrow A=2\)

alibaba nguyễn
17 tháng 11 2016 lúc 11:33

\(\sqrt[3]{5\sqrt{2}+7}-\sqrt[3]{5\sqrt{2}-7}\)

\(=\sqrt[3]{1+3\sqrt{2}+6+2\sqrt{2}}-\sqrt[3]{-1+3\sqrt{2}-6+2\sqrt{2}}\)

\(=\sqrt[3]{\left(1+\sqrt{2}\right)^3}-\sqrt[3]{\left(\sqrt{2}-1\right)^3}\)

\(=1+\sqrt{2}-\sqrt{2}+1=2\)


Các câu hỏi tương tự
Yết Thiên
Xem chi tiết
nngoc
Xem chi tiết
Nguyễn Đan Xuân Nghi
Xem chi tiết
....
Xem chi tiết
Bùi Trần Hồng Anh
Xem chi tiết
Kurosu Yuuki
Xem chi tiết
shoppe pi pi pi pi
Xem chi tiết
manh
Xem chi tiết
Minh Bình
Xem chi tiết
Ly Ly
Xem chi tiết